ANALISIS KUALITAS LAYANAN PADA APLIKASI GRAB INDONESIA BERDASARKAN MODEL SERVICE QUALITY (SERVQUAL) DI JAKARTA - Khairunissah, Deva Sasqi; Yusran, Husna Leila; Nurzakiyyah, Ulfah; Zabitha, Wafa (STIE Mahardhika, 2026)
This study aims to analyze the impact of service quality on customer satisfaction among Grab app users in Jakarta. Service quality is measured using the SERVQUAL dimension, which consists of tangibles, reliability, responsiveness, assurance, and empathy, which is widely used to assess user perceptions of digital service performance. With the rapid increase in competition in the online transportation industry, understanding how service quality shapes customer satisfaction is crucial for maintaining user loyalty. Employed a quantitative approach, using an online questionnaire distributed to 128 respondents who actively use Grab services, measured using a Likert scale. The collected data were then processed using validity testing, reliability testing, normality testing, and simple linear regression to examine the correlation between service quality and customer satisfaction. The results showed that all items in both variables were valid and reliable. The data also met the assumption of normality. Improved service quality directly contributes to higher levels of customer satisfaction among Grab users in Jakarta, as demonstrated by the regression results, which showed a positive and significant effect on customer satisfaction, with a high coefficient value and a strong standardized beta value. The study concludes that Grab's competitiveness in the digital transportation sector is highly dependent on consistent service delivery and user-centric improvements.